Medical and Nonmedical Uses of Cannabis: Overview of Cannabis in Egypt - Heikal, Tarek Mohamed (European Journal of Applied Sciences, 2026)
The medical use of cannabis is extending across many countries. Some of them legalize its use clearly and others require licensure systems to approve treatment for eligible patients. Despite this growing interest and utilization, there remains a lack of solid scientific evidence supporting its medical use, even though cannabis has been used therapeutically for thousands of years. The aim of the following conduct is to present updated data on the potential roles of cannabis-based treatments regulations globally including Egypt against various illness conditions. The information highlighted that incorporating cannabis into the therapeutic system may offer benefits. However, in many cases, despite encouraging perspectives and outcomes, the supporting evidence remains insufficient and requires further validation. Due to social and legal barriers, the conduct of such rigorous clinical trials has been hindered, limiting the availability of high-quality evidence to guide medical practice.